Effect of Women’s Empowerment on Child Nutrition in Colombia - Castillo-Guerra, Saluma (Sociedad y Economía, 2019)
Using instrumental variables estimation, this paper estimates the effect of women’s empowerment on the nu- trition of Colombian children who are younger than five. The instruments used were the percentage of women in the Department Assembly and the House of Representatives, both instruments lagged in time. The results show that female empowerment reduces underweight and wasting by 3.52 percentage and 5.95 percentage points, respectively. These results suggest a positive association between programs related to gender equality and nutrition policy in order to design complementary policies that strengthen women’s empowerment and help improve children’s wellbeing as a byproduct.